Dynamic postural balance indices can help discriminate between patients with multiple system atrophy and Parkinson's disease - Bao, Wei; Li, Puyu; Yang, Ying; Chen, Kai; Liu, Jun (Frontiers in Neurology, 2023)
Background: Parkinson's disease (PD) patients and multiple system atrophy (MSA) patients show similar symptoms but have different clinical treatments. It will be helpful to discriminate between these two kinds of patients at early or middle stage. The purpose of this study was to study the differences of the posturographic characterization between PD and MSA patients during quiet standing and perturbed standing. Methods: A total of clinical diagnosed 42 PD patients and 32MSA patients participated in the experiment. Patients were asked to first stand on a static balance force platform and then on a dynamic balance (medial-lateral rocker) force platform to measure center of pressure (COP) trajectory during an eye open (EO) state. The posturographic parameters were obtained under the two standing conditions for statistical analysis. Results: Four posturographic variables were calculated and analyzed, namely standard deviation of COP position (SD), sway path of COP position (SP), elliptical area covering the 95% COP position trajectory (EA), sway path of COP position (SP), integral area of the power spectral density at 0-0.5Hz frequency band (PSD). Except for variable EA, other three variables are all in medial-lateral (ML) direction. In the static balance experiment, there were no significant differences with the four variables between PD patients and MSA patients. However, in dynamic balance experiment, the obtained four variables all presented significant differences between PD patients and MSA patients. Conclusion: The dynamic posturographic variables with significant differences between PD patients and MSA patients imply that MSA patients have worse postural control ability in the medial-lateral (ML) direction compared with PD patients. The obtained dynamic indices may help supplemental clinical evaluation to discriminate between MSA and PD patients.